1997
DOI: 10.1046/j.1471-4159.1997.69030930.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Nicotinic Receptors Potentially Modulating Nociceptive Transmission at the Level of the Primary Sensory Neuron: Studies with F11 Cells

Abstract: F11 cells are a dorsal root ganglion (DRG) cell line used to model the function of authentic type C, peptidergic, nociceptive neurons. The cellular events underlying the antinociceptive effects of (±)‐epibatidine, a nicotinic acetylcholine receptor (nAChR) ligand that is 200‐fold more potent than morphine, is unknown. The present study investigated the ability of cholinergic channel activators (ChCAs) to effect nAChR‐gated ion flux and modulate the release of substance P (SP), a neuropeptide identified to play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Thus, our data provide first evidence of BAM8-22-induced gene expression in DRG neuron-derived cells. F11 cells emerged as a valuable biological tool for the analysis of DRG neuron-related signaling pathways, since many studies reported striking similarities to cultured DRG neurons [25], [27], [35], [36], [37], [38], [39], [40], [41], [42], [43]. Along these lines, data from our laboratory revealed morphine-induced expression of the early growth response protein-4 via µ opioid receptors in F11 cells and cultured rat DRG neurons [29].…”
Section: Discussionmentioning
confidence: 69%
“…Thus, our data provide first evidence of BAM8-22-induced gene expression in DRG neuron-derived cells. F11 cells emerged as a valuable biological tool for the analysis of DRG neuron-related signaling pathways, since many studies reported striking similarities to cultured DRG neurons [25], [27], [35], [36], [37], [38], [39], [40], [41], [42], [43]. Along these lines, data from our laboratory revealed morphine-induced expression of the early growth response protein-4 via µ opioid receptors in F11 cells and cultured rat DRG neurons [29].…”
Section: Discussionmentioning
confidence: 69%
“…F11 (rat dorsal root ganglia neurons ϫ mouse neuroblastoma) cells are generally regarded as a suitable cell model for analyzing DRG neuron-specific signaling (Francel et al, 1987;Boland et al, 1991;Puttfarcken et al, 1997;McIlvain et al, 2006;Jung and Miller, 2008) and endogenously express DOP and MOP but not opioid receptor subtypes (Fan et al, 1992(Fan et al, , 1993. MOP-specific agonists such as DAMGO increase intracellular calcium concentrations in these cells.…”
Section: Resultsmentioning
confidence: 99%
“…These presynaptic effects mediated through small TRPV1 bearing primary afferents are consistent with previous in vitro studies. Puttfarcken et al (1997) reported the release of the small afferent peptide substance P by various nicotinic agonists in a clonal F11 dorsal root ganglion (DRG) neuronal cell line.…”
Section: Discussionmentioning
confidence: 99%